Development of Voltammetry Analysis Method of Copper Metal Ions by Solid-State Membrane with Carbon Nanotube - Suyanta Suyanta; Sunarto Sunarto; Regina Tutik Padmaningrum; Karlinda Karlinda; Illyas Md. Isa; Rahadian Rahadian (Indonesian Journal of Chemistry, 2021)
This study was aimed to develop a method for metal analysis in continuous integration using voltammetry techniques. The research subject was copper(II) ions. The objects of research were linearity, scan rate, repeatability of readings, and the presence of Cu(II) levels in well water samples. In this study, a selective electrode was developed with a solid membrane voltammetry system using differential pulse voltammetry measurement. The results showed the regression line of voltammetry method, y = 10.265 ln (x) + 330.47, with a correlation value of 0.9654, the optimum scan rate was 10 mV/s, and within five repetitions of each measurement for one electrode, it showed good repeatability. Meanwhile, the result of regression with the UV-Vis spectrophotometric method for Cu(II) was y = 0.12386x + 0.00879 with a correlation value of 0.9943. The voltammetry method was found to be much better than the UV-Vis method because it was able to be used for analysis up to a concentration of 6.35 × 10–4 ppm (or 1.00 × 10–11 M), while the UV-Vis method was only able to analyze up to 1.5 ppm (or 2.36 × 10–5 M).